The Effect Of The Use of Aluminum Fiber As A Partial Substitution of Fine Aggregate on The Compressive Strength of Concrete - Nur Azizah Affandy; Muklis Sucahyo; Agus Pindo Basuki (CI-TECH, 2022)
The Effect Of The Use of Aluminum Fiber As A Partial Substitution of Fine Aggregate on The Compressive Strength of Concrete